Vocabulary builder model for autistic children / Maryam Rastikazerooni - Maryam , Rastikazerooni (2021)
Most children with autism suffer from impairments in specific cognitive processing styles, social skills, and communication skills, which affect the academic performance of those children in pre-school. The difficulties in language comprehension and communication skills result in the lack of motivation, attention, satisfaction, and interaction in this population, thus causing the children to encounter deficits in learning and especially learning vocabulary. Many Mobile-Based interventions (MBI) have been developed to address the deficits in this population. However, there are very few vocabulary builders’ software which focus on improving the vocabulary learning skills as well as providing consistent motivation for autistic children. Therefore, the aim of this study is to develop a new Mobile-Based Intervention Vocabulary Learning Model using the Picture Exchange Communication System (PECS) and Digital Storytelling (DS) together to help children with autism in acquiring English vocabulary learning skills. In this study, the design science research method (DSRM) was used which is a 6-step method for developing and evaluating the prototype. This study developed an MBI English vocabulary learning model, implemented as a prototype Mobile-based system and the system was conducted to evaluate the performance of children and usability of the prototype by 10 autistic pre-school-aged students. The evaluation results show that the software prototype is very useful, effective, and of a usable performance to help in addressing the vocabulary learning deficits in this group of kids. The autistic students showed significant improvement in terms of word learning performance and retention after using the MBI English Vocabulary learning for 3 weeks (15 sessions). More comprehensive models for learning vocabulary comprehension with sentence construction are considered for future work.